Performance enhancement of DCCP TCP - like over long delay link networks - Awang Nor, Shahrudin; Hassan, Suhaidi; Ghazali, Osman; M. Kadhum, Mohammed; Omar, Mohd Hasbullah (International Association of Computer Science and Information Technology Press (IACSIT Press), 2012)
The performance of DCCP TCP-like degrades significantly over long delay link networks.Despite the TCP-like congestion control mechanism follows the TCP SACK, the performance is really affected by the congestion window growth algorithms as employed by Jacobson based TCP variants. In this paper, all the experiments are done using Network Simulator ns-2, and we manipulated the congestion window size drop during congestion avoidance phase to enhance the performance of DCCP TCP-like over long delay link networks. Instead of halving the current congestion window when congestion events are detected, the reduction of current congestion window drop has been shown to improve the DCCP TCP-like throughput with minimal drop packet percentage.